UPAYA PENINGKATAN KETERAMPILAN BERPIKIR KREATIF MENGGUNAKAN MEDIA STEAMID DENGAN PENDEKAATAN STEAM MATERI BANGUN DATAR - Agustina, Leyna Dw; Yuniawatika; Lilyana Abiba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Creative thinking skills are the ability to generate new, original, and beneficial ideas. This ability is very important for students to face the challenges of the 21st century. However, based on initial observations and classroom experience, it was found that fourth-grade bilingual students at SD Laboratorium Kota Malang still demonstrate a level of creative thinking skills that needs improvement. The main problems lie in students' lack of mastery in the thinking process, students often rush to give answers without conducting in-depth exploration of ideas, a lack of ability to ask challenging (probing) questions, and difficulty in building upon each other's ideas. The material used is plane figures, specifically quadrilaterals. This research is quantitative with the type of research being Classroom Action Research (CAR). The subjects of this research are fourth-grade bilingual students in the 2024/2025 academic year, even semester. The research instruments include essay tests on creative thinking skills, with an average score of 77.8% obtained in cycle I and 87.5% in cycle II, with a gain score category of 0.44, falling into the medium category. It is concluded that STEAMID media with a STEAM approach can improve the creative thinking skills of SD Laboratorium UM Kota Malang students, which was obtained from observations of students' artwork in building their dream traditional houses to develop creative skills through the aspects of fluency, flexibility, originality, and elaboration.